2017
DOI: 10.9755/ejfa.2016-10-1387
|View full text |Cite
|
Sign up to set email alerts
|

Effects of different light quality on growth, photosynthetic characteristic and chloroplast ultrastructure of upland cotton (Gossypium hirsutum L.) seedlings

Abstract: The objective of the present study was to evaluate the effects of different light emitting diodes (LEDs) on growth, photosynthetic characteristic and chloroplast ultrastructure of upland cotton (Gossypium hirsutum L.) seedlings. Seedlings of the cultivar Sumian 22 were grown under seven different lights including blue (B) plus red (R) LEDs BR (1:8, 1:3, 1:1, 3:1), B LEDs, R LEDs and fluorescent lamps (FL) with the 100 μ mol m -2 s -1 photosynthesis photon flux (PPF) and a 12 hour photoperiod for 40 days. Compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
5
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 38 publications
5
5
1
Order By: Relevance
“…This is consistent with the results of a study on cucumber leaves [63]. Upland cotton (Gossypium hirsutum L.) seedlings grown under B LEDs also showed high integrity of the chloroplast ultrastructure with a clearly visible lamellar structure Li [64]. This may be related to the expression of several chloroplast-encoded genes that require B light [65].…”
Section: Discussionsupporting
confidence: 89%
“…This is consistent with the results of a study on cucumber leaves [63]. Upland cotton (Gossypium hirsutum L.) seedlings grown under B LEDs also showed high integrity of the chloroplast ultrastructure with a clearly visible lamellar structure Li [64]. This may be related to the expression of several chloroplast-encoded genes that require B light [65].…”
Section: Discussionsupporting
confidence: 89%
“…In contrast, the R light was unlikely cause the feedback of stomatal openings [37] but tended to inhibit the export of photosynthetic products [39]. Modal studies found that monochromic B light resulted in the depletion of starch and soluble sugars in leaves, while monochromic R light was prone to reserve foliar carbohydrates [40][41][42]. In our study, shoot starch concentrations showed a simple increase with the increase of the R-light proportion.…”
Section: Physiology and Carbohydratescontrasting
confidence: 46%
“…6W1-B3), which was consistent with the results of previous studies done on cucumber leaves [64]. Li [65] also reported that upland cotton (Gossypium hirsutum L.) seedlings grown under B-light-emitting diodes also showed high integrity of the chloroplast ultrastructure with a clearly visible lamellar structure. This may be related to the expression of a number of chloroplast-encoded genes requires high irradiance B light [66].…”
Section: Discussionsupporting
confidence: 91%